Emotional competency and quality enhancement process in skilled-based teaching and learning programmed at Malaysian community colleges - Don, Yahya; Daud, Yaakob; Kasim, Abd Latif; Sakdan, Mohd Fo'ad; Awang, Mohd Isha; Kasim, Kamaruddin (UniversityPublications.net, 2013)
The purpose of this paper is to discuss the influence of emotional competency on the quality of teaching and learning of lecturers in Community Colleges of Malaysia.The research implemented is in quantitative form, using cross-sectional survey approach to collect data related to current situation of emotional competency and teaching and learning qualities of research respondents. This research sample involves 563 lecturers from Community Colleges of Malaysia.Research instrument used is Emotional Competency Inventory questionnaire (ECI-2) (Boyatzis, 2001) and Teaching and Learning Quality (Noraini Idris et a., 2010).Research data analysis was done using SPSS (Statistical Package For Social Science) version 16.0 software.Data analysis was in descriptive form involving respondent descriptions such as frequencies and percentages, while the second part of the analysis consists of inference with the purpose of testing research hypothesis using Pearson correlation test, T Test, ANOVA and Regression.Research findings show that there is a positive and significant relationship between emotional competency and teaching and learning quality of Malaysian Community College lecturers. Reseach outcomes indicated that emotional competency plays an important role in influencing teaching and learning qualities of Malaysian Community College lecturers.In view of that, the self awareness, social awareness, self management and relationship management groups should be considered as important elements in planning for programs to upgrade the level of skills and reinforcing teaching and learning qualities of lecturers which directly contribute to improving achievement qualities of students in Malaysia.